Fatty acid epoxidation by Collariella virescens peroxygenase and heme-channel variants - González-Benjumea, Alejandro; Carro, Juan; Renau-Mínguez, Chantal; Linde, Dolores; Fernández-Fueyo, Elena; Gutiérrez, Ana; Martínez, Angel T. (Catalysis science & technology, 2020)
Enzyme-driven oxygenation reactions are in the spotlight for organic synthesis. In this regard, a heme-thiolate unspecific peroxygenase (UPO) from the fungus Chaetomium globosum has recently proven to be a suitable catalyst for selective epoxidation of unsaturated fatty acids in the context of the bio-based industry, but this enzyme could not be expressed in Escherichia coli for directed mutagenesis studies. Here, a previously unknown UPO from the related Collariella virescens (synonym: Chaetomium virescens ) was obtained by E. coli expression of a putative upo gene. The activity of the purified enzyme on unsaturated fatty acids with different lengths and unsaturation degrees was tested. The ability of C. virescens UPO to epoxidize these compounds increases in the order myristoleic acid (C14:1) < palmitoleic acid (C16:1) < oleic acid (C18:1) differing from that observed for the C. globosum UPO, which also forms less hydroxylated derivatives. Given the possibility to produce the C. virescens UPO in E. coli as a recombinant enzyme and its oxyfunctionalization ability, some mutated variants were obtained mimicking the active-site of C. globosum UPO and evaluated on 18-carbon unsaturated fatty acids. Results revealed that widening the heme-access channel of C. virescens UPO by substituting a phenylalanine residue (in a F88L variant) maintains the enzyme epoxidation activity, and reduces undesired hydroxylation side-reactions (from 34% to only 7% of linoleic acid products) approaching the oxyfunctionalization pattern obtained with C. globosum UPO, although maintaining the absence of diepoxides. Conversely, its partial occlusion by introducing a second phenylalanine residue (in a T158F variant) resulted in partial selective epoxidation of linoleic acid (C18:2), while the oleic acid epoxidation was prevented. The above results show how E. coli expression can speed up the availability of new UPOs, and the design of ad hoc variants of these self-sufficient monooxygenases.